1990
DOI: 10.1007/bf02776821
|View full text |Cite
|
Sign up to set email alerts
|

The destructive effects of sclerosant ethanolamine oleate on mammalian vessel endothelium

Abstract: Ethanolamine oleate (EO) used widely in sclerotherapy against esophageal varices was studied for its pharmacological effect on blood coagulation and vascular damage in animals. Blood coagulation was completely inhibited by EO at a concentration of 0.31%. EO destroyed the endothelial cells of the vessel of dog and rat within one minute after injection into the vessels. An accumulation of fibrin and platelets on the surface of the damaged vessel was observed electron microscopically. Mural thrombus was formed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
4

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 9 publications
0
14
0
4
Order By: Relevance
“…The pharmacologic effect of EO is owing to the destruction of endothelial cells, accumulation of fibrin and platelets on the surface of the damaged vessel, occlusion of the blood stream, and shrinking of the obstructed thrombus through organization [3]. Possible complications of the sclerotherapy with EO include hemoglobinuria and hemolytic renal failure, but it has been reported that if the applied dose is less than 9.6 mL, these complications do not occur [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pharmacologic effect of EO is owing to the destruction of endothelial cells, accumulation of fibrin and platelets on the surface of the damaged vessel, occlusion of the blood stream, and shrinking of the obstructed thrombus through organization [3]. Possible complications of the sclerotherapy with EO include hemoglobinuria and hemolytic renal failure, but it has been reported that if the applied dose is less than 9.6 mL, these complications do not occur [5].…”
Section: Discussionmentioning
confidence: 99%
“…The sclerosing agent, EO, is a surfactant and has been used endoscopically in the treatment of esophageal varices [3,4]. The pharmacologic effect of EO is owing to the destruction of endothelial cells, accumulation of fibrin and platelets on the surface of the damaged vessel, occlusion of the blood stream, and shrinking of the obstructed thrombus through organization [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of EIS by the intra-variceal injection method depends on the time that sclerosants at high concentration are in contact with endothelial cells in blood vessels. 11 With EISL, however, sclerosants are not diluted after release of the balloon and they work effec- tively because blood flow in the varix is completely interrupted by ligation of the injection site immediately after the injection of sclerosants. At the time we first used this method, we noted its marked effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…SRS is embolized and closed overnight, and the balloon catheter is removed on the next day. The dose of 5% EOI should be no more than 0.4 ml/kg per session of B-RTO to prevent complications such as renal dysfunction [11]. We apply the glucose push method (with 50% glucose solution) to advance the sclerosant to the side of the supplying vessel using as small a dose of 5% EOI as possible [12].…”
Section: B-rtomentioning
confidence: 99%